DEVELOPMENT STRATEGY MANGROVE ECOTOURISM BASED ON LOCAL WISDOM - Syafri Harto; Rd Siti Sofro Sidiq; Okta Karneli (Sosiohumaniora, 2021)
Mangrove Bandar Mangrove mangrove ecotourism in the urban area of Dumai is an attraction between local and international tourists. The uniqueness of Bandar Bakau mangrove ecotourism is the school of nature, the potential for flora and fauna and its mangrove forests. Ecotourism Bandar Bakau is still relatively new, the division occurred in 1999 by community leaders and managed by non-governmental organizations and local communities. Mangrove ecotourism has 24 types of species and not all of their potential can be used to increase ecotourism because of the ability of people who do not understand, the high expectations of mangrove township communities for mangrove ecotourism make ecotourism management difficult to control professionally, so awareness is needed to build an agreement in building strategies local wisdom-based ecotourism development, therefore a mangrove ecotourism development strategy based on local wisdom is needed in Bandar Bakau. This study used a qualitative approach with descriptive methods and the data were analyzed using SWOT. The technique of determining the informants was purposive sampling with observation and in-depth interviews. The research results that have been analyzed illustrate that an alternative strategy for developing mangrove ecotourism based on local wisdom yields 4 important points, first to develop mangrove conservation and rehabilitation as a form of new tourism potential in mangrove ecotourism in Bandar Bakau, second to increase participation and empowerment based on local wisdom of the local community, third formulate regulations and policies to preserve mangroves based on local wisdom of the Malay community,